Microbubble-Induced Serotonin Secretion in Human Platelets - Malmgren, R; Thorsen, T; Lie, R T; Holmsen, H (Thrombosis and Haemostasis, 1991)
The effect of nitrogen (N2) microbubbles on platelets resembles that of common platelet agonists with respect to aggregation (Thorsen T et al., Undersea Biomed Res 1986; 13:289-303). In the present study we examined the effect of microbubbles on platelet secretion of preloaded 14C-serotonin. We demonstrate that stirring of platelet-rich plasma with N2-microbubbles causes a loss of single platelets that is associated with secretion. However, secretion did not increase above baseline values until after 20 min of microbubble exposure, when platelet aggregation had reached 40%. After that time the secretion rate increased. There was no correlation between secreted serotonin and the degree of platelet aggregation. Although no 14C-serotonin secretion occurred in presence of acetylsalicylic acid (ASA), microbubble-induced platelet aggregation was only marginally reduced. Epinephrine alone caused significant platelet aggregation but no 14C-serotonin secretion and it enhanced N2-microbubble-induced platelet aggregation and secretion; ASA completely prevented secretion under these circumstances but failed to abolish the enhancement of aggregation compared with microbubbles alone. Earlier studies have shown that platelets adhere to the bubble surfaces (Thorsen T et al., Undersea Biomed Res 1987; 14:45-59). The results in the present study indicate that non-adhering platelets in the bulk phase are not activated by means of autocrine stimulation through dense granule material.